Case of multiple furuncular myiasis in Northeast Ethiopia. Issue 7 (11th July 2022) - Dires, Abebe; Kebede, Assen; Gedamu, Sisay; Dires, Tadila
Abstract: Human myiasis is a neglected disease caused by parasitic infestation of the skin, cavities, and other body parts by larvae (maggots) of a wide variety of dipteran flies. Here, we present a case of multiple furuncular myiasis caused by Cordylobia anthropophaga in a 61‐year‐old woman from Northeast Ethiopia. Abstract : Obligate myiasis by Cordylobia species is common throughout tropical areas from Africa. It can occur at any age of the life and clusters of furuncular lesions in which the white end of a maggot can be seen indicating this infestation. It is self‐limiting but can result in secondary infection.